O-29 A cluster randomised controlled trial on the effects and costs of advance care planning in elderly care. (1st September 2015) - Overbeek, Anouk; Rietjens, Judith AC; Jabbarian, LJ; Billekens, P; Hammes, Bud J; Meer, M Hansen-van-der; Polinder, S; Severijnen, J; Swart, S; Vergouwen, M; Witkamp, FE; van der Heide, Agnes; et al.
Abstract : Background: It is unclear to what extent frail older people are interested in participation in Advance Care Planning (ACP). Aim: Within the context of a research project to assess whether ACP improves Patient Activation and Quality of Life of frail older people, we assessed how many frail older people are interested in participation and how many complete the ACP program. Methods: We are conducting a cluster-RCT (2013–2016) among Dutch older people residing in 16 care homes or receiving home care. Persons in the intervention group receive the Respecting Choices® ACP program in addition to usual care. Together with a relative, they are assisted by a nurse facilitator in reflecting on health care goals and values, and encouraged to appoint a proxy decision-maker and to complete an AD. The control group receives care as usual. Results: Of 757 eligible persons, 199 (26%) consented to participate: 101 in the intervention group and 98 in the control group. Main reasons for non-enrollment were: "not interested" or "feels too old". Personal recruitment (instead of a letter) increased enrollment. In the intervention group, 87 persons fully completed the ACP program (of whom 80 completed an AD); 10 completed the program partly, and 4 declined. Discussion/conclusion: A minority of frail older people was interested in participating in a project to study the effects of ACP. Personal recruitment proved to be essential to adequately inform and include this target group. As the large majority of participants completed the ACP program, it seems that it was well received.